UPAYA PEMERINTAH KABUPATEN SIAK DALAM MENANGGULANGI PERMASALAHAN KETENAGA LISTRIKAN DI KECAMATAN LUBUK DALAM TAHUN 2011-2012 - Yulian Fazly; Erman " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Electricity problems that occur in Siak during maximal unresolved. The existence of several barriers and issues is certainly the need for a solution so that the public can enjoy the power that has been the hope of society. This is because the electric current has become a staple for the community. PLN has prepared 30 Mega electricity needs are expected to be able to meet the power needs of the community while waiting for gas Siak be operated.The lack of socialization Act No. 30 of 2009 on electricity and Government Regulation No. 14 of 2012 led to the electricity service in Siak Less max. Government Regulation No. 14 of 2012 to accommodate the electricity supply business license for its own needs. This study uses the law No. 30 of 2009 on ketenagalisrikan. This research was conducted in the Kanto district head Lubuk In, Office of the Department of Mines and Energy Siak. The data used in this research is data Primary and secondary data. The technique of collecting data through in-depth interviews and documentation.From the results it can be seen that the electricity problems that occurred in the District Lubuk Dalam is emberikan good service, in the form of electricity policy, supervision and cooperation with PLN electricity, and electricity which causes problems, economic factors, factors of population growth and development factor of inequity.Keywords: Electricity, Government, Lubuk Dalam.